Alternative forwarding strategies for geographic routing in wireless networks. (2018) - Tsai, Jung-Tsung; Han, Yunghsiang S.
Greedy forwarding (GF), the fundamental geographic routing scheme, is locally optimal on advancement distance per hop. Instead, we propose a forwarding scheme outperforming GF on total advancement distance to destination through routing decision made from neighbour positions with one-step forward expectation. We then consider that a wireless network topology consists of two subareas of different node densities and that a packet originated in one subarea is destined for the other. Routing over a least hop count path in such a network reflects the Fermat's principle. Like refraction of light at the interface between two media of different refractive indices, we derive our Snell's laws and propose geographic refraction routing (GRR) schemes. Results show that when network settings and source-destination pairs provide for obvious refraction, refraction operation can slightly shorten mean path hop counts for reliable routing but significantly improve routing success probabilities for best-effort one.